Recent advances on novel periodontal drug delivery system (World Journal of Current Medical and Pharmaceutical Research, 2022)
Periodontitis is an infectious disease resulting in inflammation the supporting within tissues of the teeth,    progressive attachment loss and bone loss-carranza. Some of the etiology and risk factors are Microbial factors, local factors, systemic factors,   genetic factors and behaviour factors. Periodontitis can occur at any age, most frequently observe in adults at the age of 30-35years.   It involves the degeneration of periodontal ligaments, resorption of alveolar bone resulting in the disruption of the structure of the teeth. In global population nearly 10-15% of people are suffering with severe periodontitis according to WHO. In management of periodontal infection Antibacterial agents are most widely used. Widening of PDL space, generalised loss of alveolar bone are the radiographic feature. Treatment requires more aggressive surgical care. Because of abundant source, lack of toxicity and high tissue compatibility the Biodegradable polymers are extensively employed in periodontal drug delivery devices. In the last decades, the treatment has been optimized for the use of drug delivery systems to the periodontal pocket, with the advantage of delivering the drug in the specific site, sustaining and/or controlling the drug concentration. Recently, the use of new drug delivery systems has been receiving great interest. This review approaches the main delivery systems for the administration of drugs to the periodontal pocket, their usefulness as well as the advancement of these systems effectiveness in the periodontal therapy.